Abundance and Diversity of Zooplankton Communities in the Littoral Waters of Al-Habbaniya Lake, Iraq - Rabee, Adel Mashaan (Al-Nahrain Journal of Science, 2018)
This study was carried out on littoral waters of Al-Habbaniya Lake to obtain baseline data on the biodiversity of zooplankton from May 2013 to March 2014 at four different study sites. Sixty–seven taxa of zooplankton were found in Al-Habbaniya Lake. of these, 46 belonging to rotifera, 13 to cladocera, and 8 to copepoda. Rotifera was the dominant group (69%), followed by copepoda (25%) and cladocera (6%). The predominant spp were Keratella cochlearis, K.valga and Brachionus calyciflorus from rotifera,while Diaphanosoma brachyurum and Bosmina longirostris were the most dominant species from cladocera. Water temperature, dissolved oxygen and pH were the main environmental variables which influenced zooplankton abundance in the lake. Shannon-Wiener diversity index ranged from 0.7 (copepoda) to 2.8 (rotifera), species richness inex ranged from1 (copepod) to 4 (rotifera) and evenness index fluctuated between 0.60-0.84. This meant that the species were evenly distributed in all sites sampled. Based on these findings, it is concluded that the relatively high zooplankton species diversity in the Al-Habbaniya Lake is an indication that the ecosystem of this lake is characterized as a ‘steady state’ type.